2009
DOI: 10.1136/ard.2008.102533
|View full text |Cite
|
Sign up to set email alerts
|

The 10-year follow-up data of the Euro-Lupus Nephritis Trial comparing low-dose and high-dose intravenous cyclophosphamide

Abstract: The data confirm that a LD IVCY regimen followed by AZA-the "Euro-Lupus regimen"-achieves good clinical results in the very long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
272
2
26

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 476 publications
(307 citation statements)
references
References 17 publications
7
272
2
26
Order By: Relevance
“…These figures in the worst-case scenario were 79%, 70%, and 66%, respectively. These are 10% lower compared to studies from the westerndeveloped nations as well as Asian-developed countries such as Hong Kong and Japan (2,3,(5)(6)(7)(8). However, these are much better than those reported from our country previously.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…These figures in the worst-case scenario were 79%, 70%, and 66%, respectively. These are 10% lower compared to studies from the westerndeveloped nations as well as Asian-developed countries such as Hong Kong and Japan (2,3,(5)(6)(7)(8). However, these are much better than those reported from our country previously.…”
Section: Discussioncontrasting
confidence: 79%
“…Absence of remission and occurrence of a major infection remained significant on multivariate analyses. Failure of induction has consistently been the most important factor that determines prognosis in studies on outcomes including prospective trials, such as Euro-Lupus Nephritis Trial (3)(4)(5)(6)(7)10,17,20). Similarly, many studies have found serum creatinine at onset and hypertension to be important prognostic factors (4,6,7,17,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include increased disease recognition with more sensitive diagnostic tests, earlier diagnosis and treatment [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Standardtherapie für die schwere Lupusnephritis ist weiterhin Cyclophosphamid, allerdings in der reduzierten Euro-Lupus-Dosis von insgesamt 3 g (6 × 500 mg) Gesamtdosis [22,23]. Darunter ist das Risiko des irreversiblen Ovarialversagens offenbar verringert.…”
Section: Nephritis Und Zns-beteiligungunclassified